Implementasi Metode Markerless Pada Aplikasi Augmented Reality Pembelajaran Geometri Untuk Siswa SD Berbasis Android - Aditya Tri Herdiansyah; Kecitaan Harefa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Learning geometry material requires a medium to visualize the shapes of geometric shapes. Learning geometry material in elementary schools still uses printed books so that students have difficulty visualizing geometric shapes because they only see through 2-dimensional images in books. This resulted in a lack of interest in learning elementary school students in studying geometry. Although these obstacles can be overcome by making crafts, especially on geometric objects, there are some drawbacks such as requiring costs to make geometrical crafts and requiring sufficient space to store geometrical crafts. The solution that can be done to overcome this is to design an application to assist in the teaching and learning process by utilizing Augmented Reality technology. The purpose of designing this application is to help students visualize geometric shapes and increase students' interest in studying geometry material. The results of this study are in the form of an Augmented Reality application for learning geometry with the Android-based Markerless method which can help students visualize geometric shapes with the results of testing the target user, which is 82.6%. In addition, this system can increase students' interest in learning with the results of testing the target user, namely 86.1%, so that the eligibility criteria for this application are "Very Feasible".